Primary Cutaneous Mammary Analog Secretory Carcinoma With ETV6-NTRK3 Translocation. (November 2016) - Amin, Sapna M.; Beattie, Adam; Ling, Xia; Jennings, Lawrence J.; Guitart, Joan
Abstract : Abstract: Mammary analog secretory carcinoma (MASC) is a recently described tumor of the salivary glands named for its morphological and molecular similarity to secretory carcinoma of the breast. Many primary carcinomas arising from the adnexal glands also share similar morphology to those arising from the breast. Brandt et al first described primary cutaneous MASC in 2009 and since then only 2 other cases have been reported. Herein, we describe a long-standing mass on the arm of an otherwise healthy 40-year-old female. Histologic examination revealed a circumscribed but unencapsulated, nodular tumor composed of bland epithelial cells arranged in solid and microcystic growth patterns. The cells showed vacuolated cytoplasm and round to oval nuclei with vesicular chromatin. Intraluminal homogenous eosinophilic secretions were present. Mitotic figures were not identified. The tumor cells stained positive for CK8/18, CK7, and S100 but were negative for other markers performed, including estrogen receptor, progesterone receptor, HER2/neu, paired box 8 (PAX8), and thyroid transcription factor 1 (TTF1). As the patient clinically had no other masses or known carcinomas, a diagnosis of primary cutaneous MASC was rendered. The ETV6-NTRK3 fusion transcript was subsequently detected by reverse transcriptase polymerase chain reaction amplification, further supporting the diagnosis. We present this case to review the histologic features of MASC and highlight the importance of recognizing this lesion not only as a possible cutaneous metastasis but also as a primary cutaneous tumor.